Insights from developing and evaluating the NHS blood choices transfusion app to support junior and middle-grade doctor decision making against guidelines. - Dhesi, AS; Wyatt, JC; Estcourt, LJ; McSporran, W; Allard, S (Wiley, 2022)
Objectives: To: 1. Develop a CE-marked smartphone App to support doctors' concordance with transfusion guidelines in non-bleeding adult patients, emphasising informed consent and anaemia management. 2. Test App accuracy and potential to improve user decisions.